Students’ Perception in The Use of Instagram for Academic Speaking Skill Learning - Pratiwi, Putri Zara Bella (RETAIN : Journal of Research in English Language Teaching, 2023)
Acquiring academic speaking skills is crucial for language learners to develop student's academic achievements. However, it becomes the most challenging aspect of language acquisition since students' mother tongue is not English. The emergence COVID-19 pandemic has further hindered students' language acquisition. Instagram, as an advanced technology and social media, is discussed as a potential tool for language learning and enhancing academic speaking skills. The study aims to investigate students' perception of Instagram as a tool for learning academic speaking skills. This research is descriptive quantitative which used a close-ended questionnaire as an instrument to elicit students’ perception. The questionnaire distributed via google forms by Slovin's formula to 70 students of English education 2019 in one of the University of Surabaya, East Java. The mean score and frequencies were presented. The result showed positive results, and most students perceived that Instagram could be used for learning and practicing English academic speaking skills. The positive perception is reflected in the average mean scores obtained across all three perception components (conative 3.8, affective 3.9, and cognitive 4.1). Based on the results above, Instagram is considered as a valuable platform for learning and practicing English academic speaking skills.